2018
DOI: 10.1016/j.bbagen.2018.03.010
|View full text |Cite
|
Sign up to set email alerts
|

Polyethylene glycol promotes autoxidation of cytochrome c

Abstract: Cytochrome c (Cyt c) was rapidly oxidized by molecular oxygen in the presence, but not absence of PEG. The redox potential of heme c was determined by the potentiometric titration to be +236 ± 3 mV in the absence of PEG, which was negatively shifted to +200 ± 4 mV in the presence of PEG. The underlying the rapid oxidation was explored by examining the structural changes in Cyt c in the presence of PEG using UV-visible absorption, circular dichroism, resonance Raman, and fluorescence spectroscopies. These spect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 55 publications
3
6
0
Order By: Relevance
“…In addition, the study proposed a model showing that heme is dislocated due to dehydration of some surface exposed hydrophobic residues i.e. Ile81 and Val83; however their spectroscopic techniques showed no significant changes 31 and are comparable to our results at lower concentrations. They have used small concentrations of PEG 4 kDa, however we are dealing with macromolecular crowding and its effect on the protein we have used variable concentrations (low to high) of the same molecular weight of PEG in similar conditions but through different approaches.…”
Section: Introductionsupporting
confidence: 85%
See 4 more Smart Citations
“…In addition, the study proposed a model showing that heme is dislocated due to dehydration of some surface exposed hydrophobic residues i.e. Ile81 and Val83; however their spectroscopic techniques showed no significant changes 31 and are comparable to our results at lower concentrations. They have used small concentrations of PEG 4 kDa, however we are dealing with macromolecular crowding and its effect on the protein we have used variable concentrations (low to high) of the same molecular weight of PEG in similar conditions but through different approaches.…”
Section: Introductionsupporting
confidence: 85%
“…1 A,B). Previously it has been reported that PEG 4 kDa of small concentrations has little change without any shift in Soret absorption and oxy-deoxy band in cyt c 31 . The studies claim that PEG 4 kDa promotes auto-oxidation of cyt c , however changes are observed to be insignificant 31 .…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations